Determination of DNA adenine methylation in genomes of mammals and plants by liquid chromatography/mass spectrometry1. Issue 79 (28th August 2015) - Huang, Wei; Xiong, Jun; Yang, Ying; Liu, Song-Mei; Yuan, Bi-Feng; Feng, Yu-Qi
<x xml:space="preserve">Abstract</x> Determination of DNA adenine methylation in genomes of mammals and plants.